Antioxidants in postmenopausal osteoporosis treatment - Paz Ibarra, José (2015)
Postmenopausal osteoporosis is the most common presentation of bone disease and is caused by estrogen deficiency that promotes bone resorption, increased osteoclastogenesis and osteoclast activity secondary to an inflammatory state due to activation of proinflammatory signal chains, increased synthesis of proinflammatory cytokines and production of reactive oxygen species. The use of antioxidants present in the diet (ascorbate) or drugs (N-acetyl cysteine and nitroglycerin) has proven to be beneficial in promoting or preserving osteoblastic function, recommending their use as part of the management of osteoporosis in postmenopausal women.